Obstacles in the Implementation of Online Loans in Indonesia (Based on Protection Law Consumer) - Sigalingging, Bagas Pratama; Putri, Anggya Nurmala; Yusnita, Ummi (Justice Voice, 2023)
Online loans are platforms that allow individuals or businesses to apply for and obtain loans over the internet. Online loans offer convenience and accessibility. However, there are also illegal online loans that are harmful to their users. This is the background for the emergence of two problem formulations, namely how legal regulations governing the practice of online loans and how consumer legal protection in online loans. The research method used is normative juridical. The results found that Financial Services Authority (Otoritas Jasa Keuangan/OJK) as the responsible authority has issued Financial Services Authority Regulations (Peraturan Otoritas Jasa Keuangan/POJK) No. 77/POJK.01/2016 on Information Technology-Based Money Lending and Borrowing Services. However, the implementation and effectiveness of this regulation is still a big challenge. Many online lending platforms operate without a license and ignore the applicable regulations, thus posing a high risk to consumers. Recipients of online loans can be said to be consumers because they are users of a service. In this case, online loan services, consumer protection has been regulated in Law No. 8 of 1999 of Consumer Protection, and regarding consumer protection in online loans has also been regulated in POJK No. 77/POJK.01/2016 and Bank Indonesia Regulation No. 3 of 2023 on Bank Indonesia Consumer Protection, although there are already regulations governing online loan consumers, online loan consumer protection is still a problem because many illegal online loans are always looking for loopholes and circumvent existing regulations.